EFFECT OF MICRONUTRIENTS AND ORGANIC MANURES ON SESAME - ELAYARAJA, D. (Journal of Ecobiotechnology, 2018)
A field experiment was carried out in a coastal farmer’s field, to study the effect of NPK level, micronutrients and organics on the soil nutrient availability, microbial population, enzyme activity and yield of sesame. The various treatments included were, T1-100% NPK (Farmer’s Practice), T2-125% NPK, T3-150% NPK, T4-125% NPK + CCP @ 12.5 t ha-1, T5-125% NPK + FYM @ 12.5 t ha-1, T6-150% NPK + CCP @ 12.5 t ha-1, T7-150% NPK + FYM @ 12.5 t ha-1, T8-125% NPK+CCP @ 12.5 t ha-1+ZnSO4 @ 25 kg ha-1 + MnSO4 @ 5 kg ha-1, T9 -125% NPK+FYM @ 12.5 t ha-1+ZnSO4 @ 25 kg ha-1 + MnSO4 @ 5 kg ha-1, T10-150% NPK+CCP @ 12.5 t ha-1+ZnSO4 @ 25 kg ha-1 + MnSO4 @ 5 kg ha-1, T11-150% NPK+FYM@ 12.5 t ha-1+ZnSO4 @ 25 kg ha-1 + MnSO4 @ 5 kg ha-1. The results of the study clearly showed that the yield benefit of the treatment T8, the application of 125% NPK along with composted coirpith @12.5 t ha-1 + ZnSO4 @ 25 kg ha-1 and MnSO4 @ 5 kg ha-1 superior in increasing the soil nutrient availability and yield of sesame.